A dimensão ética do turismo sustentável - Souza, Karoline Ketilin Moura (2013)
The association of the concept of tourism with the sustainable development had the aim of reducing the negative effects and highlighting the positive aspects which this activity could cause to the local communities and to the environment. However, due to the non-agreement among the concepts developed inside the Academy and the tourist actions available in the work market, Mario Beni has called attention to the necessity of deep studies related to the terminologies and concepts largely used in the area. Taking into consideration Beni s ideas and the afford of The World Committee on Tourism Ethics to make the principles of the Global Code of Ethics for Tourism known and the sustainable development possible, this work has as main objective to analyze the ethical dimension of the sustainable tourism according to its highest regulator (WTO). For its realization, were cataloged the following specific objectives: to analyze how the transformations of the ethical principles in technological age focus on the relationship of man with nature and in his social relations; pretend to respect for a new ethic that makes the environment favorable to human development; investigate the ethical foundations of sustainable tourism based on the documents and publications of the World Tourism Organization (WTO). This research required, above all, the methodology of the analysis of text. To base their discussions on ethics and environmental ethics, were analyzed the propositions of Larrère and Larrère, Leff, Rousseau, Santos, Serres and, mainly, of Hans Jonas. On sustainable development, the researches of Sachs, and Leff. To understand the dynamics of tourism, were considered the works of the following scholars: Beni, Krippendorf, Panosso Netto, Dias, Ruschmann, Coriolano, Philippi and Ruschmann, Fennel and Malloy. In addition to these sources, were used publications in international journals that make reference to the theme, such as: Journal of Vacation Marketing, Annals of Tourism Research, Journal of Business Ethics, Revista Estudios y perspectives en turismo. And, as a main source, were analyzed the statements coming from the major conferences of the World Tourism Organization on tourism and sustainability, in addition to the deliberations of the Committee of Ethics for Tourism. The results of this study will encourage the analysis on the concepts of value that predominate in the formulation and planning of public policies, as well as in adoption by local communities and the private sector, strategies for management of sustainable tourism. It also aims to enable the understanding on which the ethical considerations implicit in the development of this activity. Providing an understanding about how tourism promotes the sustainable use, or stimulates principles for an environmental ethics on the part of the actors involved: local community, public bodies and private, as well as tourists.